Faktor-Faktor Yang Mempengaruhi Kecenderungan Kecurangan Pengadaan Barang/Jasa (Studi Kasus Pada Satuan Kerja Perangkat Daerah (SKPD) Di Kabupaten Buleleng) - Ida Ayu Putu Krisna Dewi; Gst. Ayu Ketut Rencana Sari Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of procurement committee income, procurement systems and procedures, internal control systems, quality of procurement committees, and procurement committee ethics on the tendency of fraudulent procurement of goods/services at SKPD in Buleleng Regency. This research is a quantitative study using primary data obtained from questionnaires given to respondents. The population of this study were all Heads of Offices, Secretaries, Heads of Subdivisions (Heads of General Subdivisions , Heads of Planning  Subdivisions, Heads of Finance Subdivisions), and 1 employee from 21 SKPD in Buleleng Regency totaling 126 people. The sampling technique in this study used a saturated sample of 126 respondents. The data analysis technique used is descriptive statistical test, classical assumption test and multiple linear regression analysis using SPSS 20.0 for Windows. The results of this study indicate that the procurement committee has a negative effect on the tendency of fraudulent procurement of goods/services, the procurement system and procedure has a positive effect on the tendency of fraudulent procurement of goods/services, the internal control system has a negative effect on the tendency of fraudulent procurement of goods/services, the quality of the procurement committee has a positive effect on the tendency of fraudulent procurement of goods/services, and procurement ethics have a negative effect on the tendency of fraudulent procurement of goods/services.